2006
DOI: 10.1158/0008-5472.can-05-4128
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Driven Evolution of Immunosuppressive Networks during Malignant Progression

Abstract: Tumors evolve mechanisms to escape immune control by a process called immune editing, which provides a selective pressure in the tumor microenvironment that could lead to malignant progression. A variety of tumor-derived factors contribute to the emergence of complex local and regional immunosuppressive networks, including vascular endothelial growth factor, interleukin-10, transforming growth factor-B, prostaglandin E 2 , and soluble phosphatidylserine, soluble Fas, soluble Fas ligand, and soluble MHC class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
297
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(312 citation statements)
references
References 99 publications
8
297
0
7
Order By: Relevance
“…Specifically, many tumors as well rely on the induction of IL-10 and other immune suppressive cytokines to dampen type 1 immune responses and to remain immune evasive. 65 In a fashion similar to that of the tumor, although it is believed that mycobacteria may simultaneously use multiple mechanisms of immune evasion including mechanisms of down-regulating antigen presentation, 42,61 in the current study we have shown that IL-10 is one of the essential mechanisms through which the immune suppressive environment of mycobacterial granuloma is maintained. Despite the overwhelming evidence to support a direct role of mycobacterial infection in inducing IL-10 production by APCs, [37][38][39]62 it is plausible for us to consider the possibility that some level of IL-10 may be actively induced as part of host immune regulatory mechanisms as a means to limit immunopathology, a concession that could be exploited by mycobacteria and has recently been suggested by others.…”
Section: Discussionmentioning
confidence: 56%
“…Specifically, many tumors as well rely on the induction of IL-10 and other immune suppressive cytokines to dampen type 1 immune responses and to remain immune evasive. 65 In a fashion similar to that of the tumor, although it is believed that mycobacteria may simultaneously use multiple mechanisms of immune evasion including mechanisms of down-regulating antigen presentation, 42,61 in the current study we have shown that IL-10 is one of the essential mechanisms through which the immune suppressive environment of mycobacterial granuloma is maintained. Despite the overwhelming evidence to support a direct role of mycobacterial infection in inducing IL-10 production by APCs, [37][38][39]62 it is plausible for us to consider the possibility that some level of IL-10 may be actively induced as part of host immune regulatory mechanisms as a means to limit immunopathology, a concession that could be exploited by mycobacteria and has recently been suggested by others.…”
Section: Discussionmentioning
confidence: 56%
“…The activation status of tumor-associated macrophages may also be critical, with Stat-1 expression, essential for IFNγ signaling, an apparently adverse prognostic factor (14). Although prognosis is complicated by combining pathogenesis with response to therapy, these findings place FL-associated macrophages in line with other tumor-associated macrophages that have been shown to promote tumor progression (15) by multiple pathways, possibly including suppression of immune responses (16).…”
mentioning
confidence: 55%
“…Success of mAb therapies in the clinic is limited by several underlying mechanisms including underappreciated TME-mediated host immune response suppression, such as reduced malignant cell killing by CD8 þ CTLs and/or NK cells, and properties of some immune cells harboring protumor activities (25). In addition, tumor cells have been shown to use multiple immunosuppressive mechanisms to avoid host immune attack, including tumor-induced impairment of antigen presentation (41,42), secretion of immunosuppressive and growth factors (e.g., TGFb and IL10) in the TME (43,44), amplification of receptor tyrosine kinases (45), upregulation/expression of negative costimulatory signaling molecules (CTLA-4 binding CD80 and/or CD86, PD-L1 and/or PD-L2) by tumor cells (46,47), inhibition of dendritic cell differentiation and maturation (44,46), and increased infiltration of regulatory T-cells (48,49). Here, we demonstrate that an HA high tumor ECM enables formation of a protective pericellular matrix coat capable of inhibiting access of NK cells to tumor cells in vitro as well as antibody and NK cell access in vivo, suggesting a novel mechanism for cancer cells to escape detection and clearance by antibody-and NK cell-mediated ADCC.…”
Section: Discussionmentioning
confidence: 99%